Untapped aspects of mass media campaigns for changing health behaviour towards non-communicable diseases in Bangladesh - Reshman Tabassum; Guenter Froeschl; Jonas P. Cruz; Paolo C. Colet; Sukhen Dey; Sheikh Mohammed Shariful Islam (BMC, 2018)
Abstract In recent years, non-communicable diseases (NCDs) have become epidemic in Bangladesh. Behaviour changing interventions are key to prevention and management of NCDs. A great majority of people in Bangladesh have low health literacy, are less receptive to health information, and are unlikely to embrace positive health behaviours. Mass media campaigns can play a pivotal role in changing health behaviours of the population. This review pinpoints the role of mass media campaigns for NCDs and the challenges along it, whilst stressing on NCD preventive programmes (with the examples from different countries) to change health behaviours in Bangladesh. Future research should underpin the use of innovative technologies and mobile phones, which might be a prospective option for NCD prevention and management in Bangladesh.